2014
DOI: 10.3390/ijerph110403972
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress Scores among Saudi Students Entering Universities: A Prospective Study during the First Year of University Life

Abstract: In this prospective study we wanted to determine whether perceived stress over time among students in the Preparatory Year of King Saud University (KSU) predisposes them to cardiometabolic abnormalities. A total of 110 apparently healthy Saudi students (35 men and 75 women enrolled during the 2010−2011 academic year) were included. Perceived stress was determined at baseline and 1 year later. Anthropometrics were obtained and morning fasting serum glucose, lipid profile and cortisol were measured at both times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
(39 reference statements)
1
20
1
2
Order By: Relevance
“…In a similar study conducted at KSU preparatory year deanship, Al-Daghri 11 found that perceived stress was high at baseline among preparatory year students, which supports our findings. However, perceived stress and cortisol levels remained constant in both genders.…”
Section: Discussionsupporting
confidence: 89%
“…In a similar study conducted at KSU preparatory year deanship, Al-Daghri 11 found that perceived stress was high at baseline among preparatory year students, which supports our findings. However, perceived stress and cortisol levels remained constant in both genders.…”
Section: Discussionsupporting
confidence: 89%
“…More traditional studies analyze the predictive capacity of students' pre-university variables on academic success, concluding that High School GPA (HSGPA) results on standardized achievement tests (SAT-ACT) and socioeconomic status are significant predictors of first year students' (FYS) achievement and permanence until graduation [8]. Another broad set of studies analyze the predictive capacity of students' socio-personal characteristics (e.g., personality, learning styles and strategies), contextual influences (e.g., family support, financial difficulties), FYS experience variables (e.g., academic and social integration), and the effectiveness of actions taken by universities to foment students' learning and involvement [9][10][11]. Recent meta-analytical studies highlight the incremental validity of these variables on precedents predicting both academic achievement and permanence [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, besides these scales, this research used biological markers that may identify the intensity of physiological stress via saliva cortisol. This methodology has been widely applied in recent studies 14,22,26 . The correlation between cortisol levels and QVA-r domains reveals the influence of the students' adaptation with their levels of stress.…”
Section: Discussionmentioning
confidence: 99%